2004
DOI: 10.1007/s00775-004-0541-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationships in platinum–acridinylthiourea conjugates: effect of the thiourea nonleaving group on drug stability, nucleobase affinity, and in vitro cytotoxicity

Abstract: The synthesis, cytotoxicity, and nucleoside binding of some platinum-acridinylthiourea conjugates derived from the prototypical compound [PtCl(en)(ACRAMTU)](NO3)2 ("PT-ACRAMTU"; en=ethane-1,2-diamine, ACRAMTU=1-[2-(acridin-9-ylamino)ethyl]-1,3-dimethylthiourea, protonated form) are reported. To establish structure-activity relationships within this class of compounds, systematic changes were made to the thiourea nonleaving group, which links the intercalator to platinum. Three new derivatives of ACRAMTU, one d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 14 publications
0
42
0
1
Order By: Relevance
“…In addition, many tumor cells display intrinsic or acquired resistance to platinum (Pt)-based drugs, thus further limiting their use [6][7][8]. Hence, intensive efforts have been channeled towards the discovery of alternative Pt-based anticancer agents [9,10]. Of the several thousand Pt compounds synthesized, only about 35 have entered clinical trials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many tumor cells display intrinsic or acquired resistance to platinum (Pt)-based drugs, thus further limiting their use [6][7][8]. Hence, intensive efforts have been channeled towards the discovery of alternative Pt-based anticancer agents [9,10]. Of the several thousand Pt compounds synthesized, only about 35 have entered clinical trials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of replacing PEt 3 in compound 1 with bulkier phosphine ligands was to enhance the metal's selectivity (and potentially tolerability) by reducing its chemical reactivity. As ligands trans to phosphine, eight thioureas containing N-heterocyclic chromophores of varying basicity, borrowed from our extensive library of ACRAMTU derivatives, were introduced: 9-aminoacridines L1, L2, L5 (pK a ≈ 9−10, DNA intercalating), 15,16 1,2,3,4-tetrahydro-9-aminoacridine (tacrin) L3 and -4-aminoquinoline L4 (pK a ≈ 9−10, nonintercalating), 17,18 9-aminoacridine-4-carboxamides L6 and L7 (pK a ≈ 8), 19 and 9-substituted L8 (pK a ≈ 4, nonintercalating). 20 In addition, the simple derivative 1,1,3,3-tetramethylthiourea (tmtu, L9) was also studied.…”
mentioning
confidence: 99%
“…While the structure of this adduct and its impact on DNA conformation have been studied in detail both in DNA and oligonucleotide/nucleoside models, the mechanism of its formation remains to be explored. In a recent structure-activity relationship (SAR) study [10], we demonstrated using model reactions between 1 and 2 0 -deoxyguanosine (dG) that the monofunctional adduct, [Pt(en)(ACRAMTU-S)(dG-N7)] 3+ (dG * ) forms at a significantly slower rate than adducts of classical platinum am(m)ines under similar conditions. A half-life of adduct formation of 7.5 h was determined from timedependent NMR spectra when 1 mM Pt was incubated with 3 mM of dG at 37°C [10].…”
Section: Introductionmentioning
confidence: 95%
“…In a recent structure-activity relationship (SAR) study [10], we demonstrated using model reactions between 1 and 2 0 -deoxyguanosine (dG) that the monofunctional adduct, [Pt(en)(ACRAMTU-S)(dG-N7)] 3+ (dG * ) forms at a significantly slower rate than adducts of classical platinum am(m)ines under similar conditions. A half-life of adduct formation of 7.5 h was determined from timedependent NMR spectra when 1 mM Pt was incubated with 3 mM of dG at 37°C [10]. In contrast, reactions of conjugate 1 with calf thymus DNA proceed significantly faster and are virtually complete after 12 h [6].…”
Section: Introductionmentioning
confidence: 95%